(untitled) (Research, Society and Development, 2024)
Introduction: with the advancement of technology, children’s interest in electronic devices has increased, impacting their development. Therefore, the Brazilian Society of Pediatrics published recommendations for screen exposure by age group, in order to avoid negative impacts on the pediatric population. The objective of this study is to describe the consequences of excessive screen use in children. Methodology: this is a literary review with searches in the Scielo, Pubmed, Google Scholar, VHL and EBSCO Information Services databases for articles from the last 5 years that met the established inclusion criteria. Results: 3 articles show the impacts of excessive use of screens on neuropsychomotor development, 4 articles reaffirm language delay, 5 articles relate the use of screens to sleep quality, 5 articles agree on the impairment in cognition and 4 articles highlight changes visuals. Discussion: neuropsychomotor development is subject to changes that evolve through stimuli. In this sense, the abusive use of screens directly impacts language acquisition, sleep quality, social development and causes visual problems. Conclusion: the research allowed us to verify that the use of screens in children must be regulated, as the impacts related to this can appear in the long term, harming the development of this individual. Therefore, it will be possible to avoid episodes of aggression, anxiety, antisocial behavior, insomnia, language delay and visual problems.